2019
DOI: 10.1111/jocd.13229
|View full text |Cite
|
Sign up to set email alerts
|

Vichy mineralizing water with hyaluronic acid is effective and well tolerated as an adjunct to the management of various dermatoses and after esthetic procedures

Abstract: Introduction: M89, containing 89% of Vichy mineralizing water and hyaluronic acid, has been developed to reinforce the skin barrier and to improve skin quality. Aim:To assess efficacy and tolerability of M89. Method:Observational survey of subjects with facial dermatoses or after esthetic procedures. M89 served as adjunct to conventional therapy. Clinician assessments of erythema, desquamation, irritation and patient-reported dryness, burning, itching, and stinging/tingling were conducted at baseline and 4 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Instrumental assessments confirmed that M89 M improves skin hydration and reduces TEWL, thus restoring the skin barrier, as well as reducing skin redness, a symptom of erythema and inflammation, which confirms results from a split‐face study conducted by Berardesca et al published in 2020, assessing the benefits of M89 in subjects with rosacea 17 . In another recent study conducted on M89 proposed in a topical gel formulation, M89 significantly improved clinical signs and symptoms of dermatological procedures and met the investigators' and subjects' expectations 16 . While M89 gel applied once or twice daily allows for a significant reduction of clinical signs and symptoms following esthetic procedures over a prolonged and continued period, the use of M89 mask from right after the procedure and then twice or three‐times per week allows for an immediate improvement of clinical signs and discomfort symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…Instrumental assessments confirmed that M89 M improves skin hydration and reduces TEWL, thus restoring the skin barrier, as well as reducing skin redness, a symptom of erythema and inflammation, which confirms results from a split‐face study conducted by Berardesca et al published in 2020, assessing the benefits of M89 in subjects with rosacea 17 . In another recent study conducted on M89 proposed in a topical gel formulation, M89 significantly improved clinical signs and symptoms of dermatological procedures and met the investigators' and subjects' expectations 16 . While M89 gel applied once or twice daily allows for a significant reduction of clinical signs and symptoms following esthetic procedures over a prolonged and continued period, the use of M89 mask from right after the procedure and then twice or three‐times per week allows for an immediate improvement of clinical signs and discomfort symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…Tolerance was excellent. 26 In another yet unpublished in vitro study, M89 did not impact the skin penetration of topical ivermectin, which is recognised as an effective treatment of rosacea.…”
Section: Discussionmentioning
confidence: 91%
“…[18][19][20][21][22][23][24][25] In an unpublished analysis of a global investigation concerning a subgroup of subjects with mild rosacea, M89 applied daily on the face improved clinical signs of rosacea and, according to subjects, improved their symptoms as well as skin hydration, indicating that M89 may strengthen the natural skin barrier and help to protect the skin from environmental and external aggressions. 26 The aim of our split-face study was to assess the clinical benefit of M89 compared to standard skin care in subjects with rosacea with erythema and sensitive skin after 30 days of daily use.…”
Section: Introductionmentioning
confidence: 99%
“…7,12,15 In a study by Tan et al, M89 was shown to be effective and well tolerated as an adjunct treatment for various dermatoses and following esthetic procedures. 16 The study included patients from multiple countries and their exposure to exposome factors may differ when compared to Canada. In our study, dermatologist and patient evaluations were conducted between September 2018 and January 2019 -a period where harsh environmental/exposome factors (i.e., cold temperature in Canada) can have additional significant negative effects on skin barrier integrity and severity of the dermatoses evaluated.…”
Section: Discussionmentioning
confidence: 99%